PENGARUH KONSENTRASI GIBERELIN SINTETIS TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PARE (Momordica charantia L.) - Burhan, Zulfikar; Ramli, Ramli; Burhanuddin, Burhanuddin (AGROTEKBIS, 2018)
The decreasing of Bitter Melon production in Tojo Una-Una regency is not only caused by the lack of fertilizer distribution but also lack of cultivation because the level of pest attack is very high. Soil fertility decrease caused by several factors, they are lack of farmer knowledge about the rest of the crop cultivated such as rice straw, bitter melon and other plant species. Therefore, the research was conducted using growth regulator of Gibberellins Synthesis Gibro 10SP with active ingredient of Gibberelic Acid of 10% to set the growth and yield of Bitter Melon . The objective of this research is to find out the effect of Gibberellins Synthesis Gibro 10SP with active ingredient of gibberelic acid of 10% in each sachet to growth and production of Bitter melon, to reduce the use of inorganic fertilizer in Bantuga village of Ampana Tete District of Tojo Una-Una regency and conducted from May to July 2016. The research design used a block randomized design with one factor is the ratio of Gibberellins Synthesis concentration. G0: Control, G1: 30 ppm GA3 Synthesis/liter water, G2: 40 ppm GA3 Synthesis/liter water, G3: 50 ppm GA3 Synthesis/liter water, G4: 60 ppm GA3 Synthesis/liter water, and G5: 60 ppm GA3 Synthesis/liter water. The concentration with 6 treatments was repeated 3 times, so the total number of research units were 18 units. The variables observed were number of leaves, stem diameter, age during flowering,       length of fruit, age at harvest and weight of fruit. Total for 3 times harvest of Bitter Melon with 175 land area of research is 38  or 38,000.00 . If the land area is 1  then it is obtained the result of 2,171